Frequency Analysis of Agricultural drought of Maize in Sabie River catchment in South Africa - Masereka, Eric M.; Ochieng, George M.; Snyman, Jacques (Jàmbá: Journal of Disaster Risk Studies, 2019)
Maize (Zea mays L.) is a staple food in South Africa. Under dryland farming, drought is a major limiting factor for maize production. The yield of maize is drastically reduced when rainfall is limited and erratic during the growing season. In order to formulate strategies of reducing the impact of drought on maize production, it is necessary to analyse the magnitude and frequency of drought. The objective of this study was to carry out the magnitude and frequency analysis of agricultural drought events of maize in the Sabie River catchment in order to formulate methods of reducing the impact of drought on maize production in the catchment. The maize growing season in the Sabie River catchment begins in October and ends in February the following year. In this study, the maize growing season was divided into three growing periods based on the month maize is planted. The growing periods were: October to December, November to January and December to February. Simple water balance model in the root zone was applied to determine the minimum amount of rainfall required to meet the water requirement of maize in each growing period in all the eight rainfall zones into which the Sabie River catchment is divided. Empirical frequency analysis and stochastic frequency analysis of the agricultural drought events of maize were carried out. From the study, the return period of agricultural drought events of maize was found to be different for each rainfall zone, and the growing period ranges from 1.78 years to 2.68 years. These results are important for hydrological modellers in that they show that it is necessary to determine the best fit probability distribution for frequency analysis of hydrological events rather than assuming one as the best fit. In all rainfall zones, maize was least prone to drought in the growing period of October to December. Based on the results of the study, development of water resource infrastructure for irrigation and adoption of drought-tolerant varieties of maize was recommended to reduce the high risk of agricultural drought of maize in the Sabie River catchment.
Keywords: agricultural drought.; water balance model; empirical frequency analysis; stochastic frequency analysis